A fuzzy-PID series feedback self-tuned adaptive control of reactor power using nonlinear multipoint kinetic model under reference tracking and disturbance rejection. (February 2022) - Aftab, Adnan; Luan, Xiuchun
Graphical abstract: Highlights: Two point kinetic model used with three groups of delayed neutron precursors. Exploring actuator motor limitations effect in choice of optimized controller gains. Fuzzy controller with online auto-tuning of PID controller in series feedback scheme. Weighted output scheme in fuzzy control with curve fitting hypothesis. Handling of accidental reactivity variations and model uncertainties. Abstract: In this work, a series feedback combination of fuzzy and PID controllers is designed to resolve the reactor power control problem for VVER-1000 PWR. A nonlinear multipoint kinetic model based on neutron diffusion, thermal hydraulics, spatial neutronics and poison effect developed for dynamic simulation with three groups of delayed neutrons. PID controller design is accompanied with the variable gains depending upon the reactor power level and error power concerning a defined reference value. Piece-wise linearity and curve fitting is used to find a linear variation of gains and incorporated in the fuzzy control design. The optimum values of PID gains are based on the Matlab Tools, desired performance indices of response and the critical limitations of control output for accommodating the actuator motor boundaries. The proposed fuzzy-PID adaptive control model found preferable in load tracking application and disturbance rejection conditions in comparison with PID and fuzzy controllers in standalone configuration.